A Comparative Study on Value Added Ratios of Ultratech Cement Ltd and Ambuja Cement Ltd - Ashish Premjibhai Chirodiya (Journal of Social Commerce, 2022)
This is a comparative study of Ultratech Cement Ltd and Ambuja Cement Ltd. For the comparison Value Added Statement and Value-Added Ratios are used. For the purpose of calculation of Value-Added Statement and Value-Added Ratios data was taken from the annual reports of both companies from 2017-18 to 2021-22. For the purpose of data analysis T-test is used. Important findings of this study are that 4 ratios out of 5 are showing that there is no significant difference between the performance of both companies.